Towards a compact and precise sample holder for macromolecular crystallography. Issue 10 (10th October 2017) - Papp, Gergely; Rossi, Christopher; Janocha, Robert; Sorez, Clement; Lopez-Marrero, Marcos; Astruc, Anthony; McCarthy, Andrew; Belrhali, Hassan; Bowler, Matthew W.; Cipriani, Florent
Abstract : New compact and precise cryogenic sample holders for macromolecular crystallography are proposed as possible future European standards. Abstract : Most of the sample holders currently used in macromolecular crystallography offer limited storage density and poor initial crystal‐positioning precision upon mounting on a goniometer. This has now become a limiting factor at high‐throughput beamlines, where data collection can be performed in a matter of seconds. Furthermore, this lack of precision limits the potential benefits emerging from automated harvesting systems that could provide crystal‐position information which would further enhance alignment at beamlines. This situation provided the motivation for the development of a compact and precise sample holder with corresponding pucks, handling tools and robotic transfer protocols. The development process included four main phases: design, prototype manufacture, testing with a robotic sample changer and validation under real conditions on a beamline. Two sample‐holder designs are proposed: NewPin and miniSPINE. They share the same robot gripper and allow the storage of 36 sample holders in uni‐puck footprint‐style pucks, which represents 252 samples in a dry‐shipping dewar commonly used in the field. The pucks are identified with human‐ and machine‐readable codes, as well as with radio‐frequency identification (RFID) tags. NewPin offers a crystal‐repositioning precision of up to 10 µm but requires a specific goniometer socket. The storage density could reach 64 samples using a special puck designed for fully robotic handling. miniSPINE is less precise but uses a goniometer mount compatible with the current SPINE standard. miniSPINE is proposed for the first implementation of the new standard, since it is easier to integrate at beamlines. An upgraded version of the SPINE sample holder with a corresponding puck named SPINEplus is also proposed in order to offer a homogenous and interoperable system. The project involved several European synchrotrons and industrial companies in the fields of consumables and sample‐changer robotics. Manual handling of miniSPINE was tested at different institutes using evaluation kits, and pilot beamlines are being equipped with compatible robotics for large‐scale evaluation. A companion paper describes a new sample changer FlexED8 (Papp et al., 2017, Acta Cryst., D73, 841–851).